Features of social and psychological adjustment in visually impaired adolescents - O.I. Vlasova; V.I. Podshyvalkina; N.V. Rodina; K.L. Miliutina; A.M. Lovochkina (Ukrainian Society of Ophthalmologists, 2019)
Background: While considering the issues of the socialization of visually impaired children, we feel it is important to note that the conditions under which they develop depend on adverse childhood experiences and whether they attend and/or live in a residential school that negatively affects adolescent's social and psychological adaptability. The problem of research on the personality development in these children is that it is difficult to separate the secondary defect developing due to reduced efficiency of the visual system from the impact of a specific developmental setting. Depending on the severity of visual impairment and whether the parental family is problem free, in Ukraine, visually impaired children usually attend a residential school, a non-residential school for visually impaired children, or a mainstream school, and are raised in the respective developmental setting. This is why it is important to determine which of these settings is most appropriate for the personality development of a visually impaired child. Purpose: To identify the impact of socialization setting of residential school, non-residential school for visually impaired children, or mainstream school and adverse childhood experiences on the adaptability of visually impaired adolescents. Materials and Methods: Ninety-five visually impaired adolescents of 15 or 16 were included in this study. Of these, 32 adolescents attended a special residential school for visually impaired children and lived there, 30 attended this school but lived with their parental family, and 33 attended mainstream schools. The study was conducted with the use of the Adverse Childhood Experience (ACE) Questionnaire as modified by one of the authors; the Rogers and Diamond Psychological Adaptation Inventory, Wasserman Social Frustration Inventory, Spielberger's State-Trait Anxiety Inventory for Adults, and Multilevel Personal Adaptability Inventory (MLPAI). Results: Using the Rogers and Diamonds Inventory, we found significant differences (Kruskal Wallis test at the level of 0.05) in adaptability, self-perception, perception and emotional comfort between groups. In addition, trait anxiety was negatively correlated with adaptability (r= -0.755, p=0.000, Spielberger Inventory) in children attending and living at the residential school. There were negative correlations of health satisfaction and social frustration (as assessed by the Wasserman Inventory) with maladjustment, non-self-acceptance, emotional discomfort, self-control and escapism as accessed by the Rogers and Diamonds Inventory (all these correlations were significant at levels of 0.005 and 0.001). For the MLPAI, the level of orientation towards moral norms of society points to the role of family upbringing in the moral development of the child, and was correlated (r= 0.461 at the level of 0.01) with health satisfaction. For the modified ACE Questionnaire, all subjects reported a history of several (three to eight) hospitalizations, with the incidence and duration of hospitalizations depending on the eye disease and the potential for disease correction. Squared chi test found significant differences between groups. The level of adverse childhood experiences was positively correlated with anxiety (+0.652) and negatively correlated with emotional comfort (-0.746) and adaptability (-0.528), but no significant correlation was found with other indices. The presence of parents' antisocial behavior worsened behavioral regulation (-0.697) and orientation towards moral norms of society (-0.586).